The distribution of vertical leaves and leaves biomass on ten mangrove species at Ngurah Rai Forest Park, Denpasar, Bali, Indonesia - I PUTU GEDE ARDHANA; I M.G. S. RIMBAWAN; PUJO NUR CAHYO; YUYUN FITRIANI; SISKA ROHANI (Biodiversitas Journal of Biological Diversity, 2018)
Ardhana IPG, Rimbawan IMGS., Cahyo PN, Fitriani Y, Rohani S. 2018. The distribution of vertical leaves and leaves biomass on ten mangrove species at Ngurah Rai Forest Park, Denpasar, Bali, Indonesia. Biodiversitas 19: 918-926. The distribution of vertical leaves and leaves biomass which forms the mangrove crown divides into three parts, namely the top part, the middle part, and the bottom part. Total amount leaves on any parts are highly variable depending on height of each species. The relationship between the height of tree with the crown thickness depended on total leaves of each crown on each species as well as the relationship between the total leaves biomass of each crown on each species, with the height and volume of tree stems, also has variation on each mangrove species. Author examined the relationship between the photosynthetic organs with non-photosynthetic organs, especially on stems in each species. The high total amount of leaves and large total amount leaves biomass deeply is depended on diameter and growth height which are presented in the form of stem volumes. On the relationship between the photosynthetic organs and non-photosynthetic organs on each mangrove species, also has been examined. The higher total amount of leaves or the total amount of leaves biomass largely depended on the stem volume of mangroves. This indicates that the production of photosynthetic organ either in the form of the total amount of leaves or the total amount of leaves biomass serve to support growth of the stem mangrove trees (height of stem, diameter of stem and volume of stem).